PENINGKATAN PROMOSI DAN PENGELOLA OBJEK WISATA MELALUI PELATIHAN GMB (GOOGLE MY BUSINESS) DI KAMPUNG WISATA SANJAI BUKITTINGGI - Yesi Puspita; Ghina Novarisa; Novi Elian (LPPM Universitas Andalas, 2020)
This activity was carried out due to the lack of promotion of Sanjay village tourism through social media. Promotions using social media require managers to up-date activities as a means of promotion. Also, social media does not appear on search engines unless the public visits our social media. Furthermore, promotion is limited only to the friendships we have joined so that the public reach is only as broad as the network we have built. Therefore the GMB (google my business) application from Google can overcome the disadvantages of promotion on social media. GMB application can strengthen the promotion of the Sanjai tourist village through a Google search. Public search using keywords and also connected with google maps. This activity uses training and mentoring methods in conveying messages to management groups and entrepreneurs in the Sanjai village to become entrepreneurs in the e-commerce field. There are not many businesses in Sanjai, Bukittinggi City, not many of which have online promotion facilities. This Google My Business training is provided to equip entrepreneurs in Sanjay village to promote their merchandise digitally. In addition to this training, it was also used in developing Sanjay village tourism promotion. The result is that they are not maximal to use these applications. The many obstacles that occur in the field, such as training targets who are technologically illiterate, need mentoring efforts to carry out promotional efforts independently.